2009
DOI: 10.4196/kjpp.2009.13.5.361
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Ca2+ Activated K+ Channels, SK Channel, in the Quercetin-Induced Vasodilatation

Abstract: Effects of quercetin, a kind of flavonoids, on the vasodilating actions were investigated. Among the mechanisms for quercetin-induced vasodilatation in rat aorta, the involvement with the Ca 2+ activated K + (KCa) channel was examined. Pretreatment with NE (5 μM) or KCl (60 mM) was carried out and then, the modulation by quercetin of the constriction was examined using rat aorta ring strips (3 mm) at 36.5 o C. Quercetin (0.1 to 100 μM) relaxed the NE-induced vasoconstrictions in a concentrationdependent manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…The main finding of this study is twofold: (i) resveratrol, but not quercetin, relaxes isolated mice CC in a concentration-dependent manner through mechanisms independent of NO/sGC; and (ii) resveratrol is more potent than quercetin in reversing PA-induced decrease in nNOS responses. As resveratrol and quercetin are believed to contribute to the cardiovascular benefits of moderate red wine consumption, numerous studies have shown that both polyphenols can induce vasorelaxation [3][4][5][6][7][8][9][10]. Even in corporal tissues, positive effects to resveratrol and quercetin administration have been reported [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main finding of this study is twofold: (i) resveratrol, but not quercetin, relaxes isolated mice CC in a concentration-dependent manner through mechanisms independent of NO/sGC; and (ii) resveratrol is more potent than quercetin in reversing PA-induced decrease in nNOS responses. As resveratrol and quercetin are believed to contribute to the cardiovascular benefits of moderate red wine consumption, numerous studies have shown that both polyphenols can induce vasorelaxation [3][4][5][6][7][8][9][10]. Even in corporal tissues, positive effects to resveratrol and quercetin administration have been reported [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed on adult (8)(9)(10)(11)(12) weeks) male Swiss mice (n = 143), obtained from Janvier (Saint-Berthevin, France) or on 129SvEvS7 sGC wild type (n = 15, sGCα 1 +/+ ) or sGC alpha 1 knockout (n = 15, sGCα 1 −/− ) mice. These 129SvEvS7 mice were bred in the SPF facility of the Inflammation Research Center, VIB, Ghent, Belgium [21].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…-activated K (KCa) channels [18,19], voltage-dependent K (KV) channels [20], CFTR (cystic fibrosis transmembrane regulator) chloride channels [21], and neurotransmitter-induced current [22]. Among these paths, the large conductance Ca 2+ -activated K + (BKCa) channel has been theorized as having relevance to cell proliferation, but this assumption is still controversial [23][24][25][26][27].…”
Section: mentioning
confidence: 99%
“…For example, kaempferol shows an anti-inflammatory effect on activated macrophages [3], has chemopreventive properties in brain tumors [4], and has an suppression effect on cell proliferation in human gut cancer lines [5] [6]. Similarly, quercetin also has various pharmacological actions, including scavenging of free radicals [7]- [9], modulation of epoxyeicosanoic acid synthesis, prevention of platelet aggregation [8], and vasodilating effects [10] [11].…”
Section: Introductionmentioning
confidence: 99%